High-performance liquid chromatographic assay of serum glycated albumin - Shima, K; Ito, N; Abe, F; Hirota, M; Yano, M; Yamamoto, Y; Uchida, T; Noguchi, K (Diabetologia, 1988)
A method for determination of serum glycated albumin by high-performance liquid chromatography is presented. The system involves anion exchange chromatography to separate albumin and consecutive boronate affinity chromatography to separate glycated and nonglycated albumin. The method is rapid (20 min), precise (coefficient of variation, 0.7-4.9%), requires only a small sample (5 microliters), and can be automated. Assay of glycated albumin by this method is not influenced by the protein concentration of the sample or the presence of glucose. The variation in glycated albumin values in consecutive samples obtained within a day from diabetic patients (coefficient of variation, 2.02 +/- 0.65%) was significantly smaller (p less than 0.001) than that of values for fructosamine (coefficient of variation, 4.33 +/- 2.0%). The values of glycated albumin in normal subjects (20.2 +/- 1.6%) were clearly less than those in diabetic patients [39.6 +/- 5.4% in 40 Type 1 (insulin-dependent) and 39.4 +/- 5.9% in 25 Type 2 (non-insulin-dependent) patients]. The serum glycated albumin level was well correlated with HbA1c in 65 diabetic patients (r = 0.60). Because the life span of albumin in the circulation is short, measurement of glycated albumin should be useful as a short-term index of glycaemic control.